Problem polskiej wiary. Uwagi socjologa - Andrzej Potocki (Colloquia Theologica Ottoniana, 2014)
Author gives here the synthesis of the characteristics of religious faith Poles viewed in terms of the research workshop of sociologist. It shows that the belief is one of the indicators of religiosity and does not deplete the multidimensional nature of the latter. In the light of the research the faith of Poles is shown against the system of their life values. It turns out that faith is quite important, but not the most and the importance of it is a downward trend. In this case it is common to the Poles confess to the faith. It is also strongly marked that faith is very selective – part of it is the Church’s deposit and part of is rejected. In this way, half of declaring themselves as believers actually believe in their own way. Believers and non-believers are in fact quite similar in hierarchy of values. They differ primarily in the moral options in bioethics requirements and in the field of sexual ethics in marriage. Non-believers are marked by greater moral relativism and liberalism.